Qualidade de vida e sexualidade de mulheres histerectomizadas - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
A hysterectomy is defined as a surgical procedure in which the uterus is removed. It is one of the most performed gynecological surgeries in adult women in developed countries. Thus, the general objective of this research was to evaluate the quality of life and sexuality of women submitted to total hysterectomy using the WHOQOLBREF and the Female Quotient (QS-F); and the specific objectives were to characterize the socioeconomic and clinical aspects of women undergoing total hysterectomy; to describe the representativeness of the QoL of post hysterectomy women, from the WHOQOL-BREF instrument; analyze the impact of sexuality, through the Sexual Quotient - Women's Version (QS-F) on the life of these women; to compare the dimensions of QoL with socioeconomic and clinical aspects of the study participants. The study is descriptive exploratory, with a cross - sectional design and a quantitative approach. The population consisted of 41 women. The data were collected through interviews and application of the questionnaires to patients who underwent hysterectomy at the Mãe Luzia Women's Hospital, from 2006 to 2016, using as collection instruments a form for the socioeconomic and clinical profile and WHOQOL- BREF and the Sexual Quotient - Female Version. Statistical analysis of the data was performed in the Statistical Package for Social Sciences, version 20.0 for Windows. All results obtained by the collection instruments were transcribed into the program worksheet. The sample included 41 hysterectomized women aged 24 to 60 years - the mean age of the sample was 45.1 years (SD = 9.7 years). Brown women predominate (65.9%) and those who live with partners and children (41.5%). As for schooling, the high school completed (45.5%). As for the profession, domestic women predominated (31.7%). The family income was 3 minimum wages (36.6%). The mean time after surgery of the 41 women was 3.9 years (SD = 2.9 years); 10 (24.4%) women used hormone; 13 (31.7%) are hypertensive; 4 (9.8%) are diabetic. Regarding the risk factors, (73.2%) presented uterine fibroids. Regarding the characterization of sexual performance, there were 9 (22.0%) women with regular good sexual performance and 9 (22.0%) with good to excellent performance. There were also no significant differences between hypertensive and non-hypertensive women (p> 0.05), either in QOL or in the sexual quotient (p> 0.05). These data awaken to a new paradigm vis-a-vis the female figure, from the different social representations in which it finds itself. It was observed that the quality of life in these women was affected in some domains and the sexual performance as well. Finally, it was found that, even after the surgical procedure, their quality of life was partially affected. Thus, this study allowed us to instigate a new look at hysterectomized women, thus contributing effectively to the formation of a new social representation in the face of hysterectomy
Keywords: Histerectomia; Qualidade de vida; Sexualidade feminina; CNPQ::CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA; PROCEDIMENTOS E ATENÇÃO EM SAÚDE NO TRÓPICO ÚMIDO DA AMAZÔNIA; EPIDEMIOLOGIA E SAÚDE PÚBLICA